Efficacy and Safety of Endovascular Treatment for Acute Large-Vessel Ischemic Stroke Beyond 6 h After Symptom Onset: A Meta-Analysis - Zhongxing, Ye; Zhiqiang, Liu; Jiangjie, Wang; Qing, Chen; Jinfeng, Zhang; Chaoqun, Weng; Feng, Li (Frontiers in Neurology, 2021)
Background: There is considerable evidence on the benefits of endovascular thrombectomy (EVT) for acute ischemic stroke (AIS) within 6 h after symptom onset. However, uncertainties remain regarding EVT efficacy beyond 6 h after symptom onset. We undertook a meta-analysis to assess the efficacy and safety of EVT in patients with AIS >6 h after symptom onset. Methods: We searched PubMed, EMBASE, and Chinese Biomedical through July 2019. We included studies involving early (≤6 h) vs. delayed (>6 h) EVT in selected patients with AIS, based on radiological evaluation criteria. Functional independence, successful recanalization, mortality, and symptomatic intracranial hemorrhage (sICH) rates were assessed. Results: Eight articles, with 3,265 patients who had undergone early EVT and 1,078 patients who had received delayed EVT, were included in the meta-analysis. Patients treated with early EVT showed a similar proportion of functional independence at 90 days [odds ratio (OR) = 1.14, 95% confidence interval (CI) = 0.926–1.397, P = 0.219; I2 = 36.2%, P = 0.128] as those treated with delayed EVT. Delayed EVT was also associated with no significant difference in mortality (OR = 1.015, 95% CI = 0.852–1.209; P = 0.871; I2 = 0.0%, P = 0.527), successful recanalization (OR = 1.255, 95% CI = 0.923–1.705; P = 0.147; I2 = 60.5%, P = 0.009), and sICH (OR = 0.976, 95% CI = 0.737–1.293; P = 0.871; I2 = 0.0%, P = 0.742) rates compared with early EVT. Conclusions: Among selected patients with AIS, delayed EVT showed comparable outcomes in functional independence, recanalization, mortality, and sICH rates compared with early EVT.